2017
DOI: 10.1007/s10661-017-6025-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy and stability of variable selection methods for random forest modeling in ecology

Abstract: Random forest (RF) modeling has emerged as an important statistical learning method in ecology due to its exceptional predictive performance. However, for large and complex ecological data sets, there is limited guidance on variable selection methods for RF modeling. Typically, either a preselected set of predictor variables are used or stepwise procedures are employed which iteratively remove variables according to their importance measures. This paper investigates the application of variable selection method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 34 publications
(55 reference statements)
4
116
0
Order By: Relevance
“…Fox et al. () found that variable selection did not substantially affect model performance, relative to the model decisions explored here. Rather, variable selection tended to introduce instability in predicted probabilities (Fox et al.…”
Section: Methodsmentioning
confidence: 72%
See 4 more Smart Citations
“…Fox et al. () found that variable selection did not substantially affect model performance, relative to the model decisions explored here. Rather, variable selection tended to introduce instability in predicted probabilities (Fox et al.…”
Section: Methodsmentioning
confidence: 72%
“…, Fox et al. ). Development of CONUS‐wide predictions of biological condition required several key decisions that are not normally described in papers using RF.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations